KAJIAN PERSEPSI MASYARAKAT DKI JAKARTA SEBAGAI PENGGUNA DAN PENGEMUDI TERHADAP RENCANA PENYESUAIAN TARIF ANGKUTAN TAKSI ONLINE PADA GRAB, GOJEK DAN MAXIM - Asni Mufnizar; Budi Hartanto Susilo (Jurnal Teknik Sipil, 2022)
Technology development nowadays has brought positive impact to society including transportation aspect which has now been popularly known as online transportation. One of public online transportation massively utilize by Capital Special Region (DKI) Jakarta is special hired transportation known as online taxi, with providers are GOJEK, GRAB, and MAXIM. The increasing of online taxi driver enforce local government to conduct judicial review against applied   tariff since on Indonesia Ministerial Regulations (PM) No 118, 2018 regarding establishment of Special hired transportation the issue is not addressed yet. This research aims to obtain representative idea of applied tariff and  followed by drivers and users perception upon the issue in accordance to Mann Whitney test also BOK and Revenue analysis. Analysis was obtained that Maxim had applied the rate, whereas Gojek and Grab at any given time tariff applied beyond the upper limit. According to Mann Whitney test result, average lower tariff limit expected by the drivers is IDR3789.47/km and upper tariff limit is IDR6291.23/km, In the other hand users expecting lower tariff limit at IDR3494.41/km, and upper tariff limit at IDR5990.91/km. According to BOK the tariff obtained is at IDR2562/km. From that analysis referring to Jakarta 2022 Minimum Provincial Payment Rate to balanced income with expenditure, driver tariff expected to be set at IDR4912/km. In conclusion to tariff adjustment regulation is currently not necessary since perception and objectivities at ground is still on already maintained upper and lower limit which still covered by SK.3244/AJ.801/DJPD/2017 about upper tariff limit and lower tariff limit of Special hired transportation.